Re-Configurations Contextualising Transformation Processes and Lasting Crises in the Middle East and North Africa - Ouaissa, Rachid; Pannewick, Friederike; Strohmaier, Alena (Politik und Gesellschaft des Nahen Ostens, 2021)
This edited volume is an open access title and assembles both the historical consciousness and transformation of the MENA region in various disciplinary and topical facets. At the same time, it aims to go beyond the MENA region, contributing to critical debates on area studies while pointing out transregional and cultural references in a broad and comparative manner. The Editors Prof. Dr Rachid Ouaissa is professor of Politics of the Middle East at the Center for Near and Middle Eastern Studies at Philipps-Universität Marburg. Prof. Dr. Friederike Pannewick is professor of Arabic Studies at the Center for Near and Middle Eastern Studies at Philipps-Universität Marburg. Dr. Alena Strohmaier is postdoctoral researcher in Media and Middle Eastern Studies at the Center for Near and Middle Eastern Studies at Philipps-Universität Marburg.